The Aesthetic Doctrine of Law (Aesthetics of Law) in the Context of the Development of NBICS Technologies - Chernogor, Nikolai; Emelyanov, Alexander; Zaloilo, Maksim (Տիգրան Մեծ)
The development of NBICS technologies is one of the factors of transformation of the mechanism of social regulation, including law, which acts as a means and as an object of socio-economic modernization. The scientific search creates new contexts in the study of law, serves as a prerequisite for rethinking its essence and role in the life of modern society, determines the formulation of a number of questions, including the consequences of technological progress for the legal existence of a person. In line with this kind of research, new areas of research have been identified Ŕ “legal cognitology”, “functional identifycation of law”. One of the promising ideas is an appeal to aesthetics, more precisely, to the regularities of the development of law, which can be learned through the methodology of this field of knowledge. The subject of the article is the methodology of knowledge of the law. The purpose is to establish the possibility of expanding the methodology of knowledge of law through the methods of aesthetics and NBICS technologies. The result is a reasonable hypothesis that the development and implementation of NBICS technologies allow us to apply aesthetic methods to the establishment of the regularities of the genesis of law.
Keywords: Philosophy of law